Fracture strength and color stability of direct composite veneer using different materials (Mustansiria Dental Journal, 2022)
Aim: The purpose of this study was to compare the fracture resistance and color stability of three different restoration materials: Nano composite, flowable composite, and Nanohybid composite.Materials and Methods: 45 removed human maxillary premolar teeth for orthodontic treatment were chosen. The teeth were divided into three experimental groups, each consisting of fifteen teeth: Direct composite veneers constructed of Nano - composites were employed to fix the teeth in Group A. (Z350 XT, 3M, USA). Group B: Flowable composite was used to directly veneer teeth (G-aenial Universal flo GC, Japan). Group C: Direct composite veneers made of Nanohybid composite were used to reconstruct teeth (G-aenial GC, Japan). Each tooth in groups A, B, and C had a copyplast template made prior to preparation using a 1 mm thick vacuum-pressed polyethylene plastic template. Standard preparations (intra enamel) were made for all teeth in experimental groups using ceramic veneer set burs. By injecting flowable composite via a hole formed in a copyplast template, Group B is restored. In Groups A and C, the buccal third (Bucco-palatally) of the template was filled with restorative material using a plastic tool before being positioned on the tooth and squeezed until it made contact with the unprepared tooth surface. All specimens' baseline colors were assessed using a spectrophotometer (Vita Easyshade, Ivoclar VivadentAG, Schaan, Liechtenstin). After baseline color measurement, each group of laminate veneers were subjected to immersion solutions (Tea bags, Lipton). Each specimen's color values were once again measured with the same spectrophotometer, and the color change values (ΔE) were computed. Using a universal testing equipment, the fracture strength was evaluated.